2014
DOI: 10.1242/jeb.101196
|View full text |Cite
|
Sign up to set email alerts
|

Cold acclimation alters the connective tissue content of the zebrafish (Danio rerio) heart

Abstract: Thermal acclimation can alter cardiac function and morphology in a number of fish species, but little is known about the regulation of these changes. The purpose of the present study was to determine how cold acclimation affects zebrafish (Danio rerio) cardiac morphology, collagen composition and connective tissue regulation. Heart volume, the thickness of the compact myocardium, collagen content and collagen fiber composition were compared between control (27°C) and cold-acclimated (20°C) zebrafish using seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 36 publications
(70 reference statements)
5
47
0
3
Order By: Relevance
“…Previous studies have reported similar results in trout and zebrafish (Farrell et al, 1988;Klaiman et al, 2011;Johnson et al, 2014), and we have suggested that such a decrease in compact myocardium helps to maintain cardiac compliance at low temperatures (Johnson et al, 2014). Such an effect should translate into the heart generating lower diastolic pressures compared with a heart with more compact myocardium when measured at the same temperature, yet we observed no difference in the mean diastolic pressures between the ventricles from the 4°C-and 17°C-acclimated males.…”
Section: Variation In Morphological Remodellingsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies have reported similar results in trout and zebrafish (Farrell et al, 1988;Klaiman et al, 2011;Johnson et al, 2014), and we have suggested that such a decrease in compact myocardium helps to maintain cardiac compliance at low temperatures (Johnson et al, 2014). Such an effect should translate into the heart generating lower diastolic pressures compared with a heart with more compact myocardium when measured at the same temperature, yet we observed no difference in the mean diastolic pressures between the ventricles from the 4°C-and 17°C-acclimated males.…”
Section: Variation In Morphological Remodellingsupporting
confidence: 79%
“…These findings support the hypothesis, mentioned above, that the thickness of the compact myocardium plays a role in regulating the compliance of the ventricle. It has also been suggested that an increase in collagen content in the compact myocardium plays a role in regulating ventricular compliance (Johnson et al, 2014). However, while there was significantly more collagen in the compact myocardium of the female fish acclimated to 11°C than in males from the same acclimation group, the diastolic pressure was higher in the males.…”
Section: Sex-specific Differences In Cardiac Morphology and Functionmentioning
confidence: 97%
“…Embryos were embedded in Shandon Cryomatrix resin (Fisher Scientific, Mississauga, ON, Canada) and cryosectioned in 10 µm thick sections. Sections were either stained routinely with hematoxylin and eosin to observe basic chorion morphology, or stained with the collagen-specific dye Picrosirius Red to observe just the collagen component of the chorion using the method of Johnson et al (2014).…”
Section: Series Ii: Impact Of Rearing Environment On Early Developmenmentioning
confidence: 99%
“…2). The adult ZF heart showed typical mature muscle organisation (Johnson et al, 2014) with a predominantly spongy atrial and ventricular myocardium and a small outer compact layer surrounding the ventricle ( Fig. 2A).…”
Section: Morphological and Proteomic Characterisationmentioning
confidence: 99%